A study of the correlation between Coxiella burnetii seropositivity and abortions in sheep in Eastern and Southeastern Turkey - Kilic, Ayse; Kalender, Hakan (Agricultural Research Communication Centre, 2016)
Q fever is a zoonotic disease that occurs worldwide and is caused by the obligate intracellular bacterium Coxiella burnetii. Infected animals are usually asymptomatic, but infection can cause abortion and stillbirth in ruwinants. The main purpose of this study was to evaluate prevalance of Coxiella burnetii infection in aborted and nonaborted sheep serum samples in Eastern Anatolia region by using enzyme-linked immunosorbent assay (ELISA). The determine of prevalance in sheep flocks from four provinces (Elazig, Malatya, Tunceli, Bitlis) and tested for anti-C. burnetii antibody detection, by means of Chekit Q fever Elisa kit. 350 serum samples obtained from flocks belonging aborted sheep showed that a total of 56 (16%) were detected seropositivity, whereas 171 serum samples obtained from nonaborted sheep flocks in 13 of the 171 (7.60%) for C. burnetii in seropositivity were observed. Coxiellosis should be considered an important cause of sheep with abortion history and nonaborted in Elazig and neighboring provinces.
Keywords: Abortion; C. burnetii; sheep; Serology